2013
DOI: 10.1002/jwmg.628
|View full text |Cite
|
Sign up to set email alerts
|

Population dynamics of double‐crested cormorants in two interior breeding areas

Abstract: Because of rapid population expansion, conflicts between double‐crested cormorants (Phalacrocorax auritus) and humans have increased, particularly at aquaculture facilities in the Lower Mississippi River Valley (LMRV), United States. Although key demographic information on the Interior population is sparse, management decisions for population reduction are already in place across their breeding range. New evidence suggests the Appalachian Mountains may act as a migration divide for Interior cormorants, causing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 31 publications
1
13
0
Order By: Relevance
“…; Chastant et al . ) results in potentially large overestimates of λ when the population contains nonbreeders (Fig. ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…; Chastant et al . ) results in potentially large overestimates of λ when the population contains nonbreeders (Fig. ).…”
Section: Discussionmentioning
confidence: 99%
“…Accounting for demographic differences between breeders and nonbreeders is clearly important for estimating population growth rates, but what happens if the presence of nonbreeders is unknown or ignored? The common practice of estimating demographic parameters and growth rates based solely on the breeding population (Gr€ uebler et al 2008;Katzner et al 2011b;Chastant et al 2014) results in potentially large overestimates of k when the population contains nonbreeders (Fig. 2).…”
Section: Observation Analysismentioning
confidence: 99%
“…Larger clutch sizes may also contribute to higher fledge rates, particularly when coupled with superior foraging, because larger clutches facilitate the opportunity to raise more young. Likewise, the cause for reduced fledge rate in western breeding areas is unclear, but may be linked to poor nest site quality or inadequate local foraging opportunities as the birds nesting in the west exhibit weak colony site fidelity (Chastant et al 2014). Colony differences in chick growth and development may reflect age and experience of the adults.…”
Section: Discussionmentioning
confidence: 99%
“…spring migration, and catfish comprises 87% of their diet (Glahn et al 1999). These piscivorous birds have subsequently increased their overwinter survival by improving body condition through catfish exploitation (Glahn et al 1999;Chastant et al 2014). Using sulfur isotope analysis from feathers grown during winter months, Hebert et al (2008) also suggested that if cormorants spent at least a portion of the winter foraging at aquaculture facilities, they returned to the breeding grounds in better physical condition than cormorants that solely fed in marine environments.…”
mentioning
confidence: 99%
See 1 more Smart Citation